Election Posters Around the Globe : Political Campaigning in the Public Space - Holtz-Bacha, Christina; Johansson, Bengt (Springer, 2020)
Contents: 1 Posters: From Announcements to Campaign Instruments.- 2 Theoretical Perspectives on Visual Political Communication Through Election Posters.- 3 Methodological Approaches to the Analysis of Visual Political Campaigns (1989-2013): The Same Ideas with Different Words.- 4 Australian Election Posters.- 5 Advertising Concepts in Posters of the Main Chilean Political Campaings Through the Same Ideas with Different Words.- 6 Towards a European Culture of Political Communication? Themes and Style of the Posters 2009 and 2014 European Election Campaigns.- 7 Election Posters in Finland. Cueing Emotions with Visual Imagery.- 8 French Electoral Poster Campaigns in the 21st Century.- 9 Indispensable and Very Much Alive: Posters in German Election Campaigns.- 10 Symbols, Slogans and Charisma: Political Posters in India's 2014 National Election.- 11 Under the Banner of Democracy: Political Expression in Malaysia's 13th General Election.- 12 Electoral Posters in Mexico: From Monochromatic Iconography to Multicolor Saturation.- 13 Election Posters in Poland: From Amateurish Leaflets to Professional Billboards.- 14 Election Campaign Posters: The Case of South Africa.- 15 Election Posters in Spain: An Old Genre Surviving New Media?.- 16 From Propaganda to Image Building.- Four Phases of Swedish Election Poster History.- 17 Framing Politics: The Enduring Appeal of the Poster in British General Election Campaigns.- 18 Election Posters in the United States After World War II.- 19 Election Posters Around the Globe - Conclusion.